Microfinance and Prospect for Islamic Microfinance Products: The Case of Amanah Ikhtiar Malaysia - Md Saad, Norma (World Science Publisher LLC, 2012)
Abstract - Studies have shown that microfinance is capable of reducing poverty in rural areas in several countries around the world. Microfinance products are however, still dominated by conventional products despite a demand for shariah compliant microfinance products by Muslim clients. A survey conducted in Bangladesh found that even though Bangladesh has the largest conventional microfinance outreach serving almost 8 million clients, Islamic microfinance represents only 1 percent of the microfinance market. Another survey found that in all Muslim countries, Islamic microfinance still represents a small percentage of the country’s total microfinance outreach. The survey also found that Islamic microfinance institutions lack of product diversification, offering only one or two Islamic financing products and over 70 percent of the products offered are murabahah. Islamic microfinance is still in an infancy stage in Malaysia. Commercial banks offering microfinance services in Malaysia limit their products based on bai-al inah, a controversial debt-based lending. The largest microfinance in Malaysia, Amanah Ikhtiar Malaysia (AIM), claims that its loans are based on qard-hasan (interest-free) principles, however, AIM imposes a 10% service charge on its loans. This study explores the possibility of introducing Islamic financial products to clients of Amanah Ikhtiar Malaysia. A survey was conducted on the business activities of AIM borrowers to identify suitable Islamic microfinance products to finance various types of business activities. Based on the three major economic activities of AIM clients, Murabahah, Musharakah, Mudarabah, Muzaraah, Ijarah, and Qard al-hasan principles are found to be applicable to finance the different economic activities.